“Probably a Little Bit of a Hill to Climb”: A qualitative study of emergency department providers’ perceptions of nonpharmacological pain treatment - Rogelio A. Coronado; David G. Schlundt; Kristin R. Archer; Kemberlee R. Bonnet; Carrie E. Brintz; Tyler Toledo; Vivek P. Joseph; Ruth Q. Wolever; Catherine S. Hobbs; Mira P. Patel; Sean P. Collins; Alan B. Storrow (PLoS ONE, 2026)
Background Nonpharmacological strategies are advocated as evidence-based treatment options for pain, yet these are rarely offered within the emergency department (ED) setting. Understanding how ED providers perceive these strategies can guide implementation efforts. Objective The objective of this study was to qualitatively examine ED provider perceptions of conventional and complementary nonpharmacological pain strategies. Methods Nine ED physicians from a single academic medical center completed a semi-structured interview conducted by a trained qualitative researcher. The interview focused on the provider’s current pain management approach and perceived benefits, barriers, and facilitators of nonpharmacological pain treatments. Each interview was audio-recorded, transcribed verbatim, and analyzed using an iterative deductive–inductive approach. Findings were organized into themes and subthemes to inform a conceptual model of nonpharmacological intervention implementation. Results Six major themes emerged: 1) institutional context around intervention implementation, 2) professional beliefs about nonpharmacological pain interventions, 3) patient characteristics as a modifying factor, 4) intervention characteristics as a modifying factor, 5) process of implementation, and 6) engagement. Providers acknowledged benefits of nonpharmacological strategies, particularly for patients with chronic pain or history of opioid use. However, perceived barriers included negative patient perceptions of mind-body therapies, minimal ED provider training or education, limited time or care coordination support, and lack of physical space. Possible facilitators for integration included provider education, leadership support, and intervention tailoring. Conclusion ED providers recognize the potential value of nonpharmacological pain treatment strategies. However, both broad healthcare and ED-specific barriers to implementation may limit routine use in the ED. Future efforts for improving pain management in the ED should identify strategies to address implementation barriers of evidence-based nonpharmacological interventions.